Implementation of the Principal's Managerial Function in Managing Work Programs at SMP Negeri 1 Masama, Banggai Regency - Venny Yece Roring; Jeffry S.J. Lengkong; Viktory N. J. Rotty (JR Education, 2026)
Effective school work programme management depends substantially on the principal's managerial competence in planning, organising, implementing, and controlling educational activities. This study aimed to analyse the implementation of the principal's managerial functions in managing school work programmes at SMP Negeri 1 Masama, Banggai Regency, Indonesia. A qualitative descriptive approach was employed to obtain an in-depth understanding of managerial practices within the natural school setting. Data were collected through semi-structured interviews, participant observation, and document analysis involving the principal, teachers, and administrative staff as key informants. Data were analysed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing, while trustworthiness was ensured through triangulation and credibility procedures. The findings indicate that the principal has implemented the four core managerial functions; however, their effectiveness remains uneven. Planning has been conducted through the preparation of the School Work Plan and School Activity and Budget Plan, although these documents are not yet consistently supported by comprehensive needs assessment and evidence-based decision making. Organising has established formal organisational structures and delegated responsibilities, but task allocation has not always aligned with staff competencies, and collaborative teams require stronger institutional support. Programme implementation has generally proceeded according to plan, yet coordination, stakeholder participation, and systematic monitoring remain insufficient. Furthermore, supervisory practices have been undertaken through classroom visits, administrative reviews, and programme monitoring; nevertheless, they lack structured scheduling, comprehensive documentation, and sustainable follow-up actions. These findings demonstrate that strengthening evidence-based planning, competency-oriented task delegation, participatory leadership, continuous monitoring, and systematic evaluation is essential for improving school governance and organisational effectiveness. The study contributes to the growing body of knowledge on educational management by providing an integrated managerial framework for enhancing school leadership effectiveness and supporting continuous school improvement in developing educational contexts.